Indigenous Futurisms in North American Indigenous Art: The Transforming Visions of Ryan Singer, Daniel McCoy, Topaz Jones, Marla Allison, and Debra Yepa-Pappan. Issue 1 (2016) - Baudemann, Kristina
Abstract : This article defines Indigenous futurisms as Indigenous storytelling about the future and discusses its form and function in the work of five contemporary North American Indigenous artists. This involves, on the one hand, locating Indigenous artistic expression in the complex discursive field of colonialist representations, postmodern aesthetics, and popular culture; on the other hand, Indigenous futurisms must be both linked with and delineated from Western traditions of imagining the future. The future is an ideologically inflected space and in order to establish artistic presence and envision Indigenous futures, Indigenous artists break open structures of meaning production and liberate Indigenous forms of expression from stereotyping. On the intersection of North American Indigenous realities with pop art and popular culture, and of the memory of historical trauma with Western ideologies of progress, Indigenous artists create a visual code to map out new worlds and project Indigenous sovereignties into parallel dimensions and fantastic futures.